Sustainable energy management - Golušin, Mirjana; Dodić, Siniša; Popov, Stevan (Academmic Press, 2013)
While the last few decades have witnessed incredible leaps forward in the technology of energy production, technological innovation can only be as transformative as its implementation and management allows. The burgeoning fields of renewable, efficient and sustainable energy have moved past experimentation toward realization, necessitating the transition to more sustainable energy management practices. Energy Management is a collective term for all the systematic practices to minimize and control both the quantity and cost of energy used in providing a service. This new book reports from the forefront of the energy struggle in the developing world, offering a guide to implementation of sustainable energy management in practice. The authors provide new paradigms for measuring energy sustainability, pragmatic methods for applying renewable resources and efficiency improvements, and unique insights on managing risk in power production facilities. The book highlights the possible financial and practical impacts of these activities, as well as the methods of their calculation. The authors' guidelines for planning, analyzing, developing, and optimizing sustainable energy production projects provide vital information for the nations, corporations, and engineering firms that must apply exciting new energy technology in the real world. Shows engineering managers and project developers how to transition smoothly to sustainable practices that can save up to 25% in energy costs! Features case studies from around the world, explaining the whys and hows of successes and failures in China, India, Brazil, the US and Europe Covers a broad spectrum of energy development issues from planning through realization, emphasizing efficiency, scale-up of renewables and risk mitigation Includes software on a companion website to make calculating efficiency gains quick and simple.
Keywords: Energy development.; Renewable energy sources.; renewable energy sources.; elektronické knihy; electronic books